Islamic Legal Analysis Of Istishn'a Contract Transactions In Buying And Selling Practices - Purnama Wahyuni; Riyan Sinaga (AT-TAFAHUM: Journal of Law, 2021)
This study aims to describe and analyze the Istishna Agreement, a sales transaction carried out in the form of ordering the manufacture of goods or goods with certain specifications and standards to the buyer or ordering party. In Istishna, payment can be made in advance, paid in installments until completion, or postponed until a mutually agreed date. And Istishna is usually applied to products and industrial products. The type of research used is descriptive. Data sources in this study are library research and observation. The results of this study are Istishna sale and purchase transactions that are not widely known. However, without them realizing it, this agreement has been widely realized in their lives such as pre-orders in all online shops with technological media, where they order with the criteria they agree on and then pay according to the time agreed. This sale and purchase is included in the sale and purchase that is permitted in Islam. With Fatwa Fatwa Sharia Council No: 06 / DSN-MUI / IV / 2000.